Closed Spaces: Beckett and Confinement - LITTLE, JAMES (Trinity College Dublin. School of English. Discipline of English, 2017)
This thesis is the first sustained study of Samuel Beckett?s career-long engagement with confinement, examining both his use of institutions of coercive confinement as well as the function of the closed spaces of his later prose and drama. Focussing on twenty-two case studies from Beckett?s critical, poetic, dramatic and prose writing, including the seven prose works in which institutions of confinement feature as key locales, it combines a historicist approach to institutional and performance space with the methodologies of genetic criticism (which studies an author?s manuscripts to investigate the geneses of his/her works) and spatial theory. Close readings of Beckett?s texts form the basis for a re-evaluation of his development as a writer and director. The thesis opens by studying Beckett?s use of images of confinement in the articulation of key aesthetic problems, which leads into an analysis of the role that the asylum played in the development of his poetics. I then focus on the ?decomposition? of institutional space in Beckett?s postwar prose before turning to his work in the inherently spatial art forms of performance. Beckett?s ?decomposition? of closed space became a radical disintegration when his protagonists turned from saying ?I? to ?not I?; I analyse the relation between Beckett?s voices and closed spaces in both his prose and drama. Through a study of intertextual references in some of Beckett?s most confined settings, I show that, far from cutting down our interpretative options, his closed spaces are highly productive. My final chapter argues that the study of coercive confinement provided in this thesis can give us a new understanding of Beckett as a political writer. This thesis challenges the model of Beckett?s poetics as simply involving the ?vaguening? of topography while contesting the view that his work takes place in ?empty space?. As well as giving fresh insight into Beckett?s poetics and aesthetics, confinement provides a unique lens on important topics in his writing, such as the relation between subject and object and the politics of literary representation. Due to Beckett?s use of confinement when engaging with such topics as well as his practical manipulation of space in performance, this study of his closed spaces can allow for a reconsideration of the way Beckett worked, the way his work means as well as what his works mean.
APPROVED
Keywords: Samuel Beckett; confinement; space; genetic criticism; historicism; aesthetics; poetics; politics; prison; asylum; spatial theory